Penyuluhan Pemilahan Sampah Organik dan Anorganik untuk Meningkatkan Kesadaran Lingkungan Terhadap Anak Paud Karya Bakti Medan - Wahyuni, Rifa; Rahmadani, Siti; Aprilia, Tamara Adisa; Oktavia, Hangelika; Efata, Efata; Heflindo, Heflindo; Ariani, Devi; Yusnadi, Yusnadi; Subaeda, Sitti (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to increase environmental awareness for PAUD Karya Bakti Medan children through counseling on organic and inorganic waste sorting. This study uses a qualitative approach. This research was carried out at Paud Karya Bakti which is located on Jalan karya Bakti no 124, Indra Kasih Medan Tembung District, Deli Serdang Regency. Data collection techniques were collected using interviews, observations, and documentation. The data analysis process is carried out through three stages, namely data reduction, data presentation, and conclusion drawing. The results of the analysis show that counseling on organic and inorganic waste sorting can increase environmental awareness for PAUD Karya Bakti Medan children. PAUD Karya Bakti Medan children who participated in counseling for organic and inorganic waste sorting had better knowledge and environmental awareness compared to children who did not participate in counseling. Counseling on organic and inorganic waste sorting can help PAUD Karya Bakti Medan children understand the importance of maintaining environmental cleanliness and reducing negative impacts on the environment.